1990
DOI: 10.1139/e90-039
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of sand-flat sandstone and playa–lacustrine mudstone in theTriassic–Jurassic Blomidon redbeds, Fundy rift basin, Nova Scotia: implications for tectonic and climatic controls

Abstract: The redbeds of the 220 m Blomidon Formation comprise more than 100 pairs of (i) sand-flat sandstone (distal alluvial fan) and (ii) playa sandy mudstone and (or) lacustrine claystone. These pairs are tectonic autocycles generated by rift-basin subsidence and sagging along the Glooscap fault zone that shifted loci of active fan sedimentation toward and away from the playa surface as fan lobes migrated into topographically low areas.Intervals of intense and prolonged aridity are recorded in many of the sand-flat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…The Chedabucto Formation more closely resembles the coarse clastic units of the Wolfville Formation cropping out to the west in the Minas subbasin, whereas the upper Eurydice Formation is lithologically and temporally similar to the Norian-Hettangian Blomidon Formation which overlies the Wolfville Formation. In the Minas subbasin, the Wolfville and Blomidon Formations constitute a major finingupward megasequence of alluvial-fan to braided-stream to sandflat/playa deposition resulting from basin enlargement (Olsen et al 1989;Mertz and Hubert 1990;Schlische and Olsen 1990). A similar sequence may exist in the Eurydice Formation o f the nearby Orpheus basin, consisting o f a coarse, lower member equivalent to the Chedabucto and Wolfville Formations, and a finer-grained upper member, similar to the Blomidon Formation.…”
Section: Discussionmentioning
confidence: 99%
“…The Chedabucto Formation more closely resembles the coarse clastic units of the Wolfville Formation cropping out to the west in the Minas subbasin, whereas the upper Eurydice Formation is lithologically and temporally similar to the Norian-Hettangian Blomidon Formation which overlies the Wolfville Formation. In the Minas subbasin, the Wolfville and Blomidon Formations constitute a major finingupward megasequence of alluvial-fan to braided-stream to sandflat/playa deposition resulting from basin enlargement (Olsen et al 1989;Mertz and Hubert 1990;Schlische and Olsen 1990). A similar sequence may exist in the Eurydice Formation o f the nearby Orpheus basin, consisting o f a coarse, lower member equivalent to the Chedabucto and Wolfville Formations, and a finer-grained upper member, similar to the Blomidon Formation.…”
Section: Discussionmentioning
confidence: 99%
“…10). Minerals that have been eroded to form the open spaces are also unidentified but may be described in other studies of the Blomidon Formation (Mertz and Hubert 1990;Olsen and Et-Touhami 2008). Alcock (1948) noted the presence of "minor amounts of reddish and brownish sandstone and conglomerate" a few km to the southwest of Grand Harbour, which he mapped beneath the basalt along the western side of the Red Point Fault.…”
Section: Dwellys Cove Formationmentioning
confidence: 98%
“…It might be produced by a local playa or ephemeral lake in a semi-arid climate, as in the sedimentary environment described by Mertz and Hubert (1990) for the Blomidon Formation. Wade and Jansa (1994, p. 228) reported that this lithology is not known in the Blomidon Formation beneath the basalt elsewhere around the Bay of Fundy.…”
Section: Dwellys Cove Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leleu et al 2009) and subordinate aeolian dune deposits (Hubert & Mertz 1980 and alluvial fan sediments (Hubert & Mertz 1984). The contact between the formations corresponds to a major change in facies architecture to mud-rich playa margin deposits containing evaporites and ephemeral fluvial sheetsandstones (Hubert & Hyde 1982;Mertz & Hubert 1990;Gould 2001). The extensive North Mountain Basalt, part of the Central Atlantic Magmatic Province event (McHone 2000), overlies the Blomidon Formation, and straddles the Triassic-Jurassic boundary (Olsen et al 1989;Olsen 1997).…”
Section: Fundy Basin Nova Scotia Canadamentioning
confidence: 99%